Barrero, Tomás Andrés. “Aserción, expresión y acción. Una lectura de J. L. Austin.” (2017)
Barrero, Tomás Andrés. “Aserción, expresión y acción. Una lectura de J. L. Austin.” Dianoia 60.74 (2015): 81-107.